Research on a flow-mode magneto-rheological impact damper with stroke-activated capability - Nguyen, Huu-Quan; Bui, Quoc-Duy; Nguyen, Duc-Nam; Nguyen, Quoc Hung; Hoang, Long-Vuong (Vietnam Journal of Mechanics, 2025)
It is widely recognized that impact is an intricate problem that has challenged scientific scholars for many years. Impacts, such as those occurring in high-speed aircraft landings, vehicle accidents, or machine tool operations, pose substantial hazards to human health and safety, as well as cause damage to the structural durability, integrity and sustainability of various facilities. This paper researches a flow-mode magneto-rheological (MR) impact damper (ID) to reduce the effects of shocks and vibrations during sudden impacts. By applying a magnetic field to the magneto-rheological fluid (MRF) within the damper, the damping properties can be adjusted in real-time. The traditional approaches typically use electric coils to generate the required magnetic field, leading to increased complexity and high costs in structure and control systems. To address this limitation, we replace the coils with multiple permanent magnets distributed along the linear displacement of the damper, enabling the generation of a progressive damping force. Therefore, in addition to a more streamlined design, the new configuration equips the MRID with a stroke-activated capability that aids in creating a soft-landing effect, thereby minimizing harm during collisions. To improve the operational efficiency, performance criteria of the damper, including damping force in off and activated states, dynamic range and installation volume, are considered in a design optimization procedure. Optimal solutions for the proposed MRID are simulated using the finite element method (FEM), followed by a detailed design phase. Subsequent analyses and discussions are conducted to provide guidance for future development.